2022
DOI: 10.2196/37324
|View full text |Cite
|
Sign up to set email alerts
|

Establishing Institutional Scores With the Rigor and Transparency Index: Large-scale Analysis of Scientific Reporting Quality

Abstract: Background Improving rigor and transparency measures should lead to improvements in reproducibility across the scientific literature; however, the assessment of measures of transparency tends to be very difficult if performed manually. Objective This study addresses the enhancement of the Rigor and Transparency Index (RTI, version 2.0), which attempts to automatically assess the rigor and transparency of journals, institutions, and countries using manus… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
13
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
2

Relationship

3
6

Authors

Journals

citations
Cited by 17 publications
(15 citation statements)
references
References 54 publications
0
13
0
Order By: Relevance
“…While it is still easy to find papers citing antibodies with insufficient information to uniquely identify the reagent, such as authors just citing the protein and vendor, a truly terrible practice, it is getting less common. A recent study of all accessible antibody sentences (in ∼2M documents) in the open access literature found that antibody catalog numbers or RRIDs (making them uniquely identifiable) in papers is becoming much more common, going from 12% of antibody references in 1997 to 31% in 2020 ( 16 ). It is unknown to what extent this welcome change is due to efforts of the Antibody Registry, but with over 300K antibody RRIDs in the scientific literature, the contribution is not insignificant.…”
Section: Discussionmentioning
confidence: 99%
“…While it is still easy to find papers citing antibodies with insufficient information to uniquely identify the reagent, such as authors just citing the protein and vendor, a truly terrible practice, it is getting less common. A recent study of all accessible antibody sentences (in ∼2M documents) in the open access literature found that antibody catalog numbers or RRIDs (making them uniquely identifiable) in papers is becoming much more common, going from 12% of antibody references in 1997 to 31% in 2020 ( 16 ). It is unknown to what extent this welcome change is due to efforts of the Antibody Registry, but with over 300K antibody RRIDs in the scientific literature, the contribution is not insignificant.…”
Section: Discussionmentioning
confidence: 99%
“…Like Menke et al (2022), here we used SciScore (Ver 2, RRID:SCR_016251) to check each paper that contained a reference to an animal or antibody from our exemplar stock centers. Figure 4 shows the comparison of the overall RTI vs the papers gathered that refer to one of the stock centers.…”
Section: Analysis Of the Rigor And Transparency Indexmentioning
confidence: 99%
“…Together, these approaches bring us a few steps closer to making use of new evidence at a much quicker pace. Further, measuring research quality indicators in an automated way may allow for the benchmarking of research improvement activities over time (Wang, Hair, et al, 2021;Menke et al, 2022).…”
Section: Keeping Up To Date With the Literaturementioning
confidence: 99%